ISLAMIC PUBERTY EDUCATION AND MUSLIM FEMALE IDENTITY FORMATION: EVIDENCE FROM KEPUTRIAN PROGRAMS IN MUHAMMADIYAH ELEMENTARY SCHOOLS YOGYAKARTA - Wantini; Mgr. Sinomba Rambe; Usmayanti Nur Haliza; Tahmid Miftachurrozaq (Academic Bright Collaboration, 2026)
This study explores the role of the keputrian program in supporting the formation of Muslim female identity among elementary school girls experiencing early puberty in Muhammadiyah schools in Yogyakarta. The study responds to the increasing occurrence of early puberty and menarche among primary school girls, which often occurs before sufficient emotional, social, and religious readiness has developed. A qualitative case study was conducted in three Muhammadiyah elementary schools in Yogyakarta from July to October 2025. Data were collected through interviews, participatory observations, and documentation involving 18 female students who had experienced early puberty and 6 female teachers serving as keputrian facilitators. The data were analyzed thematically through coding, categorization, and triangulation. The findings show that early puberty was experienced not only as a biological transition marked by menstruation but also as an emotional and religious transition characterized by fear, embarrassment, confusion, and uncertainty regarding bodily changes and religious responsibilities after baligh. The keputrian program provided a supportive environment where students received guidance on menstruation, purification (taharah), aurat, personal hygiene, worship practices, and appropriate social behavior. Participation in the program contributed to greater emotional confidence, improved understanding of bodily changes, increased readiness to perform religious obligations, and stronger awareness of Islamic values associated with Muslim womanhood. The findings further indicate that emotionally supportive female teachers played a central role in helping students interpret puberty as a meaningful stage of religious and personal development. The study is limited to three Muhammadiyah elementary schools and reflects context-specific experiences. This study highlights the keputrian program as a school-based Islamic puberty education model that integrates bodily literacy, emotional mentoring, worship readiness, and Muslim female identity formation, thereby extending discussions on Islamic education and early puberty in elementary school settings.